Corrosion behavior of steel in alkali-activated fly ash mortars in the light of their microstructural, mechanical and chemical characterization. (February 2016) - Monticelli, C.; Natali, M.E.; Balbo, A.; Chiavari, C.; Zanotto, F.; Manzi, S.; Bignozzi, M.C.
Abstract: This study concerns the corrosion behavior of steel in different room temperature cured alkali-activated fly ash mortars exposed to chloride solution. The corrosion process was monitored by polarization resistance and corrosion potential measurements and the results were interpreted in the light of a complete microstructural, mechanical and chemical characterization of the mortars. The most compact alkali-activated mortars have higher porosity and lower mechanical properties than a cement-based mortar (CEM), but the protectiveness afforded to the rebars is slightly higher than that obtained in CEM. The reason for this discrepancy is connected to a lower chloride content accumulated in the former mortar type and to a specific inhibition of the rebar corrosion afforded by the pore electrolyte in alkali-activated mortars.